Synthesis and characterization of sepiolite - based geopolymers - Acar, Göksu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Geopolymers are amorphous inorganic polymers that are alternatives to Portland cement (PC) due to their comparable performance such as high mechanical strength and fire resistance. Although geopolymers are traditionally alkali-activated aluminosilicate materials, in this thesis, magnesium silicate based geopolymers are studied. Sepiolite, a hydrated magnesium silicate clay mineral, is used as the main raw material. In the first part of this thesis, sepiolite-based geopolymers with varying Si/Mg ratios were synthesized and characterized by x-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and differential thermogravimetric analysis (DTGA). Compressive strength tests were employed to establish structure-performance relations in this system. XRD results revealed that an amorphous geopolymer matrix was produced including minor crystalline components. FTIR analysis showed a systematical increase of the main FTIR band indicating Si-O vibrations to higher frequencies with increasing Si/Mg ratios. Compressive strength results initially increased in the compositional range of 2≤Si/Mg≤3; reached a maximum value at Si/Mg=3; and finally decreased for geopolymers with 3≤Si/Mg≤4. It was found that addition of soluble silicon to geopolymer system initially enhances compressive strength and stability. However, excess amounts of sodium and water content results in decreasing mechanical performance. In the second part of this thesis, the effect of sodium content on the structural characteristics of sepiolite-based geopolymers with Na/Mg ratio between 0.8-2 was investigated. XRD results displayed mainly amorphous characteristics with forsterite and sodium carbonate phased appearing at higher Na/Mg ratios. FTIR band constantly decreased to lower frequencies indicating decreasing polymerization with increasing Na/Mg ratios. These results are supported by SEM images displaying the transition from a glassy surface microstructure into a form dominated by carbonates.
Keywords: Portland cement.